MODELING AND PERFORMANCE ANALYSIS OF OUTPUT ENHANCED TRANSFER FIELD (TF) MACHINE (Nigerian Journal of Technology, 2025)
The output performance of a conventional transfer field (TF) machine is low in comparison with those of other asynchronous machines. In this study, a reconfigured transfer field machine with simultaneous rotor induced currents and capacitance injection for enhancement is presented. The machine comprises two identical salient-pole machine elements that are coupled mechanically and wound integrally for the same pole number. The salient-pole half axes are displaced in space quadrature in the machine elements comprising the machine. Each stator has dual sets of identical poly-phase windings regarded as primary and secondary that are sinusoidally distributed in the stator slots. Primary windings are interconnected in series between the machine elements and the terminals connected to public utility source while the secondary windings are swapped betwixt the machine elements and then terminated on a balanced variable capacitor bank. Windings are also placed on the rotors. The mathematical model of the machine is derived, the resulting equations therefrom are simulated in MATLAB/Simulink environment. It is shown that with an optimized value of  tuned capacitor, a remarkable improvement in the performance characteristics of the machine over the traditional TF machine is obtained when compared. The starting torque, power factor and maximum torque increased by 384.2% (1.9N-m to 9.2N-m), 87.5% (0.32 to 0.6) and 374.1% (6N-m to 28.45N-m) respectively, which confirm superior performance characteristics.